Socio-demographic portrait of transsexual patients in Russia - N. V. Solov’eva; E. V. Makarova; V. B. Vil’yanov; S. A. Kremenitskaya; S. V. Chausova; I. V. Kichuk (Медицинский совет, 2019)
Transsexualism is a distress caused by a discrepancy between a person’s gender identity and sex assigned at birth. Theme of  transsexualism has a strong resonance in society today. This phenomenon is significant both for the law system and for the health  care system of the state. There is no statistics information on transgender people in Russian Federation. The author’s goal was to  draw a socio-demographic portrait of patients with an established diagnosis of transsexualism. The following conclusions were  made: the number of MtF and FtM patients searching for medical care is equal; age of the transition is 26.6 years; age of selfidentification in the opposite gender is 10.2 years; most MtF take HRT on their own initative; transsexual persons are distinguished  by a high level of education, large variety of professional activities, a low percentage of registered marriages, and comparable to the  general population onset of sexual life.